E-Commerce, Solusi di Tengah Pandemi COVID-19 - Nurlela Nurlela (Universitas Nusantara PGRI Kediri, 2021)
The 2019 Corona Virus Disease (COVID-19) pandemic which is endemic in almost all countries in the world has had an impact on economic growth. Even the conventional business sector really felt the decline in turnover until it went out of business. But it is different with the e-commerce business, which is expected to increase despite the COVID-19 pandemic. This journal aims to examine the increase in e-commerce during the pandemic through a literature study. The results of the study show that the e-commerce business in the world during the pandemic experienced a very significant increase. The e-commerce business in Indonesia has increased 10 times with the addition of more than 50% new customers during the pandemic. However, the process of sending goods experienced a slight slowdown due to transportation restrictions and restrictions from the government. The increase in the e-commerce business during the pandemic can be analyzed to have the potential to affect the increase in e-commerce in the future.